Analisis Peran Pendidikan Vokasi Dalam Pengembangan Industri Halal di Indonesia - Achta Pratama, Fahmi; Mulyadi Muslim (Risalah Iqtisadiyah: Journal of Sharia Economics, Sharia Economics Study Program, STEI Ar Risalah Sumatera Barat, 2022)
The halal industry, which is an industrial concept based on sharia economics, has great potential in the world's economic cycle. In Indonesia itself, including the largest country that adheres to Islam, has great potential in the development of the halal industry to develop. One of these development efforts, vocational education is considered to have a role in the development of the halal industry in Indonesia. Therefore, this study aims to analyze the role of vocational education in the development of the halal industry in Indonesia. This study applied the literature review method and in collecting data the researchers reviewed articles. From the results of the research conducted, it is known that vocational education plays an important role in efforts to develop the halal industry in Indonesia, because vocational education is education that concentrates on preparing graduates to work in the world of work with soft skills, hard skills, work experience and entrepreneurial urgency. The conclusion from this research is that vocational education with all its tools has a very vital role in the development of the halal industry in Indonesian.